Perceived Organisational Support: A Cross-National Comparative Study Between Ghanaian and Finnish Industrial Workers. (20th July 2015) - Gyekye, Seth Ayim; Haybatollahi, Mohammad
Abstract : Perceived organisational support (POS) refers to an employee's perception concerning the degree to which organisational management values their contributions and cares about their wellbeing. Despite the influence of culture on organisational behaviour, there is still a paucity of culture-comparative studies. The study investigated POS from a cross-national perspective with Ghanaian and Finnish industrial workers. We hypothesised and tested a model predicting differences on POS using a cross-sectional data of Ghanaian ( N = 320) and Finnish ( N = 520) industrial workers. The data were collected with Eisenberger, Fasolo, and LaMastro's (1990) Survey of Perceived Organizational Support. Correlational analyses, t -test and hierarchical regression analyses were used to test four hypotheses. The relationships between employee demographic factors and POS were also analysed. The hierarchical regression analysis revealed worker demographic variables as impacting more significantly on POS among Ghanaian workers. Contrary to our expectations, Ghanaian workers perceived more managerial support than their Finnish counterparts. Structural equation modelling revealed job satisfaction as a mediator in these relationships. Path analysis performed to identify specific variables that were moderated by culture revealed organisational position and job satisfaction as potential variables. The theoretical and practical implications of the study are discussed.